Enhancing silkworm protein yield, extraction efficiency, structure, functionality, and antioxidant activity using ultrasound-, microwave-, and freeze–thaw-assisted methods - Phuangjit, Uraiwun; Klinkesorn, Utai; Tan, Chin Ping; Katekhong, Wattinee (John Wiley and Sons, 2023)
Abstract BACKGROUND Silkworm protein applications are limited in the food industry because of their low emulsifying and foaming properties. This study investigated the effect of ultrasound‐assisted extraction (UAE) for 15 and 30 min, microwave‐assisted extraction (MAE) for 1 and 2 min, and freeze–thaw‐assisted extraction (FTAE) for one and three cycles on the yield, extraction efficiency, functional properties, and antioxidant activities of proteins from silkworm pupae. Relationships of protein structure and functionality were also examined. RESULTS UAE for 15 and 30 min and MAE for 1 and 2 min significantly increased protein yield and extraction efficiency compared to the control. Both UAE and MAE processes, especially MAE for 2 min, greatly improved the emulsifying and foaming properties of extracted proteins. FTAE one and three cycles did not increase the protein yield and extraction efficiency but showed enhanced functional properties, especially foaming. All samples showed changes in protein structure, such as increased exposed sulfhydryl (SH) contents, denaturation temperatures, and enthalpy. Only MAE samples had low‐molecular‐weight proteins based on sodium dodecyl sulfate–polyacrylamide gel electrophoresis. UAE and FTAE samples had significantly higher antioxidant activities, while the MAE process showed the opposite. CONCLUSION UAE and MAE processes improved the yield and functionality of extracted silkworm proteins, while MAE negatively impacted protein antioxidant activities. © 2023 Society of Chemical Industry.